Performance Evaluation of Oil-free Chillers for Building Energy Performance Improvement. (2015) - Yu, F.W.; Chan, K.T.; Sit, R.K.Y.; Yang, J.
Abstract: This paper investigates how to improve the energy performance of central air-conditioning systems by using oil-free chillers. Three conventional water-cooled centrifugal chillers of equal capacity were replaced by three oil-free chillers of the same capacity in an existing system. Operating data for performance evaluation were logged at 1-hr intervals for over one year before and after the replacement. The superior coefficient of performance (COP) of oil-free chillers with variable speed control brought an energy saving of 9.6% in the total electricity consumption of a shopping arcade when they operated for a wide range of system cooling demands. Results of data envelopment analysis gave an average technical efficiency of 0.6 which ascertains an opportunity for performance enhancement. The system COP can be further improved by tightening the control in the temperature of supply chilled water and implementing even load sharing among chillers to meet the overall system capacity.